2022
DOI: 10.1111/1460-6984.12748
|View full text |Cite
|
Sign up to set email alerts
|

Word‐finding behaviours in narration for typically developing French speakers of school age

Abstract: Background: Research in word-finding difficulties is sparse, especially in languages other than English. As a result, the factors associated with the frequency of word-finding behaviours are poorly understood, particularly in discourse.Aims: This exploratory study is the first to collect data relative to the expected frequency of word-finding behaviours in narration for French speakers aged 7-12 years old with typical development; and (2) to identify the factors associated with the frequency of word-finding be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 34 publications
(99 reference statements)
0
0
0
Order By: Relevance
“…difficulties in French-speaking children since previous research suggests that there may exist some differences in WF in French and in English (Bourassa Bédard & Trudeau, 2021;Bourassa Bédard et al, 2022). Our analysis suggested that modality of testing and sociodemographic variables, gender and SES did not have an impact on WF measures.…”
Section: Discussionsupporting
confidence: 42%
See 4 more Smart Citations
“…difficulties in French-speaking children since previous research suggests that there may exist some differences in WF in French and in English (Bourassa Bédard & Trudeau, 2021;Bourassa Bédard et al, 2022). Our analysis suggested that modality of testing and sociodemographic variables, gender and SES did not have an impact on WF measures.…”
Section: Discussionsupporting
confidence: 42%
“…Regarding gender, this result is unexpected for measures of WF in narration. Our previous study of typically developing children (Bourassa Bédard et al, 2022) found that boys of the same age-range produced more word-finding behaviours than girls.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations